Advancements, applications, and foundations of C++ - Ajrawi, Shams Al; Jennings, Charity; Menefee, Paul; Mansoor, Wathiq; Al-Aali, Mansoor (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series, 2024)
Many undergraduate students in computer science, engineering, and related disciplines struggle to master the complexities of the C++ programming language. Existing textbooks often need more depth and breadth to provide a comprehensive understanding, leaving students with fragmented knowledge and hindering their ability to tackle real-world programming challenges effectively.Advancements, Applications, and Foundations of C++ is a compelling solution to this problem, offering a comprehensive and accessible approach to learning C++. With eight carefully structured chapters covering fundamental and advanced topics, the book provides a scaffolded learning experience that guides students from basic concepts to more complex programming techniques. This book's target audience includes undergraduate students, professionals seeking to improve their programming skills, and educators teaching programming courses. By offering a thorough and well-rounded education in C++, this textbook aims to empower students to succeed in their programming endeavors and contribute meaningfully to the field.